Prunus - Küden, Ayzin (IntechOpen, 2020)
The book of "Prunus" contains chapters on breeding, germplasm, fruit tree physiology, and production of Prunus species, written by authors from different parts of the world. Prunus is one of the most important fruit genera widely spread according to the various climatic and soil conditions. This wide adaptability of the Prunus genus gives an opportunity for it to be grown in many parts of the world. In modern taxonomy, subgenera of Prunus such as Amygdalus, Cerasus, Laurocerasus, Lithocerasus, Padus and Prunus include many species among which Prunus persica L., Prunus domestica L., Prunus armeniaca L., Prunus avium L. are the main ones. Briefly, this book is on Prunus species, which is one of the main fruit and nursery plants grown in the world.